Open visitation in the NICU: nurses’ perspectives on barriers and facilitators† - Ghorbani Fatemeh (Frontiers of Nursing, 2023)
This study aimed to investigate the nurses’ perspectives on open family visitation and its barriers and facilitators in neonatal intensive care units (NICUs).